Design of HR Performance Measurement System Using Human Resources Scorecard Method (Case Study of PT XYZ) - Hutami, Ghina Tiyasti; Triwibisono, Christanto; Nugraha, Fida Nirmala (Proceeding UII-ICABE, 2020)
PT XYZ is one company that focuses on producing high-quality clothing for the global market, at very competitive prices. Currently, the company is only measuring performance for individuals, but there has not been a comprehensive performance measurement. One performance measurement that is able to overcome HR problems is the Human Resources Scorecard method with four perspectives, namely financial, customer, internal business process, and growth and learning. Measuring HR performance at PT XYZ using a description of the company’s vision, mission and strategy. Then the weighting uses the AHP method. Based on data processing, there are 5 strategic objectives, 9 critical success factors, 14 KPIs. The final result of PT XYZ’s performance score financial perspective is 3.278 with good criteria, customer perspective is 4,000 with good criteria, internal business process perspective is 4.197 with very good criteria, and growth and learning perspective is 3.518 with good criteria. Overall the performance of PT XYZ is 3.7591 with good criteria. Keywords: Performance Measurement, Human Resources Scorecard, Critical Success Factor, Key Performance Indicator, Analytical Hierarchy Process (AHP)